Genetic testing and eHealth usage among Deaf women. Issue 5 (10th June 2019) - Kushalnagar, Poorna; Holcomb, Juliana; Sadler, Georgia R.
Abstract: In the past decade, accessible information in American Sign Language (ASL) about cancer and genetic testing is expanding on eHealth platforms, including social network sites, commercial sites, and mobile apps. Primary data on genetic testing awareness and genetic testing for BRCA 1/2 among Deaf women were gathered using HINTS‐ASL survey between November 2016 and April 2018, and secondary data for hearing women were drawn from NCI's HINTS 5 Cycle 1 survey in 2017. Deaf women who had heard of DNA testing (63%) were more likely to be young adults, college graduates, and/or have a family history of cancer. Compared to hearing women, Deaf women who had heard of genetic testing were more likely to use social networking sites to read or share information about medical topics and watch health‐related videos. Making eHealth platforms accessible in ASL and easy‐to‐understand text can help reduce knowledge gap in genetic testing, since some Deaf women may not be using genetic testing to help identify whether they are at increased risk for breast and ovarian cancer early on, before they are diagnosed with cancer.